Do residents differentiate between the impacts of tourism, cruise tourism, and Airbnb tourism?. Issue 2 (1st February 2023) - Jordan, Evan J.; Vieira, José Cabral; Santos, Carlos M.; Huang, Ting-Yen (Tim)
Abstract: Tourism impacts the quality of life of host community residents in myriad ways. Most research seeking to understand those impacts has either focused on tourism in general or a single specific type of tourism. Little is understood about how residents attribute perceived impacts to different forms of tourism when they are present in the same community. We surveyed 995 residents of the island of São Miguel in the Azores archipelago to examine perceptions of tourism's quality of life impacts using Andereck and Nyaupane's Tourism Quality of Life Impacts scale in relation to tourism in general, cruise tourism, and Airbnb tourism. While confirmatory factor analysis (CFA) revealed poor fit of the measurement model across all forms of tourism, repeated measures ANOVA analysis of individual impact questions revealed that residents did differentiate between the impacts of various types of tourism in their community. Residents thought that tourism in general was the most detrimental to urban issues like traffic and crowding and that cruise tourism provided the least positive impacts to their community across all other TQOL variables. These findings indicate that future research on resident perceptions of tourism impacts should seek to measure impacts related to the specific forms of tourism.